Information sales and insider trading with long-lived information - Giovanni Cespa (Queen Mary University of London, Department of Economics, 2007)
Fundamental information resembles in many respects a durable good. Hence, the effects of its incorporation into stock prices depend on who is the agent controlling its flow. Like a durable goods monopolist, a monopolistic analyst selling information intertemporally competes against herself. This forces her to partially relinquish control over the information flow to traders. Conversely, an insider solves the intertemporal competition problem through vertical integration, thus exerting tighter control over the information flow. Comparing market patterns I show that a dynamic market where information is provided by an analyst is thicker and more informative than one where an insider trades.
Keywords: G10; G12; G14; L12; 330; Information sales; Analysts; Insider trading; Durable goods monopolist; Informationswert; B\~AƒÂrsenkurs; Insiderhandel; Theorie